SYSTEM OF NATIONAL SECURITY: POLITICAL AND LEGAL ANALYSIS - Pavliutin, Yu. (Honor and Law, 2020)
The article emphasizes that in the conditions of modern globalization, in order to ensure sustainable development of the national state, the exclusive ability to ensure national security must be preserved. It was stated that the slightest loss of even a part of the sovereignty is contrary to the national interest and poses a threat to the national security of the state. A number of works devoted to the conceptual, organizational, legal and institutional principles of development and implementation of the state national security policy, its origins and problems of implementation in the modern practice of state management are analyzed. It is stated that the political assessment of the effectiveness of measures to ensure national security depends on the conciseness, clarity and balance (logical conditionality) of the basic security law. It is concluded that the unity of national interests, national goals and national ideas is the basis for the formation and construction of national security policy of Ukraine, the system of national and state security, as well as the subject of further research in security administration technologies. It was emphasized that Ukraine, as an ethnic entity to ensure national security, with common national interests, national goals and national idea should have formed a stable political system, which, in turn, should ensure the formation of governing bodies of society and the state and decision-making bodies that are responsible for the issues of national and state security. It is emphasized that only within the ratio of the categories “ethnic entity of national security” and “state security” “protection of state sovereignty, territorial integrity and democratic constitutional order and other vital national interests from real and potential threats of non-military nature.” Finds its manifestation.